2011
DOI: 10.3109/02713683.2011.593727
|View full text |Cite
|
Sign up to set email alerts
|

Putative Rabbit Conjunctival Epithelial Stem/Progenitor Cells Preferentially Reside in Palpebral Conjunctiva

Abstract: Long-term retention of BrdU-labeled cells at the mucocutaneous junction indicated that slow-cycling stem cells may locate at this position. The epithelial stem/progenitor cells at the mucocutaneous junction may serve as an origination of transient amplifying cells that migrate towards the fornix. Rabbit palpebral CECs (including mucocutaneous junction epithelial cells) possess higher self-renewing ability in vitro. Collectively, conjunctival epithelial stem/progenitor cells in the rabbit may preferentially res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(12 reference statements)
1
6
0
Order By: Relevance
“…We confirmed our results with another important characteristic of stem cells, which was their potential to remain highly proliferative. These results are also consistent with another study (Su et al, 2011), reporting that rabbit palpebral epithelial cells grow faster and have more proliferative cells (likely originating from cancer stem cells with higher in vitro colony forming rates than the other parts of the conjunctiva).…”
Section: Discussionsupporting
confidence: 82%
“…We confirmed our results with another important characteristic of stem cells, which was their potential to remain highly proliferative. These results are also consistent with another study (Su et al, 2011), reporting that rabbit palpebral epithelial cells grow faster and have more proliferative cells (likely originating from cancer stem cells with higher in vitro colony forming rates than the other parts of the conjunctiva).…”
Section: Discussionsupporting
confidence: 82%
“…More recently, a study of the location of long-term BrdU label-retaining cells of the rabbit conjunctiva, reported that the BrdU-labeled cells appeared to be concentrated at the mucocutaneous junction with the authors suggesting that epithelial stem/progenitor cells at the mucocutaneous junction serve as the source of transient amplifying cells that migrate towards the fornix (Su et al, 2011). An even more recent study of human conjunctival epithelium by Stewart et al studied location of stem cell-like cells using colony-forming efficiency, expression of stem cell markers ABCG2, ΔNp63, and Hsp70 in cultures from multiple regions of the conjunctiva, as well as ABCG2 localization in fixed tissue.…”
Section: Location Of Conjunctival Stem Cells and Goblet Cell Lineagementioning
confidence: 99%
“…16,41 -44 The high MPI that we found in the fornical conjunctiva can probably be explained, as we mentioned above, by the mixed collection of conjunctival cells from the inferior tarsal -bulbar -fornix. The mucocutaneous junction of the rabbit eyelid 45,46 and the rat palpebral conjunctiva 47 have also been postulated as sources of replacement for the conjunctival epithelial cells, suggesting that the location of dividing cell populations might vary between species. In addition, stem cells with high in vitro proliferative potential are usually located in the thicker epithelial zones.…”
Section: Articlesmentioning
confidence: 99%